Is it possible to manage energy politics? Exploring the direct and indirect effects of political factors on the acceptance of solar energy - Hwang, Eunjung; Kim, Seoyong; Kim, Sohee (Energy Strategy Reviews, 2024)
Is an energy transition a rational choice? To answer this research question, this study analyzed the direct and indirect effects of political ideology and partisan support on the acceptance of solar energy by applying regression analysis and the moderation effect. The risk perception factor, energy factor, and political factor were set as the independent variables. The results showed that non-political variables such as perceived risk, perceived benefit, negative emotion, knowledge, trust, and energy insecurity influenced the acceptance of solar energy more than political variables. Negative emotion had the strongest negative effect on the acceptance. Second, support for the Moon jae-in government as a partisanship variable was associated with the acceptance of the solar energy. However, ideology had no effect on the acceptance. Third, support for the Moon Jae-in government had a positive direct effect on the acceptance and indirectly influenced it by ways of perceived benefits, trust, and negative emotion, which are key influencers of acceptance of solar energy. Progressive political ideology had no direct effect on acceptance, but indirectly suppressed the effect of negative emotion on solar energy acceptance. This study shows that partisanship, in terms of presidential support, has both direct and indirect effects on solar energy acceptance, whereas ideology has indirect effects. Given the important role of political variables, future research should focus more on various political variables, such as political leadership, preference for green politics, climate politics, and the polarization of political support as independent variables.
Keywords: Acceptance of solar energy; Energy; Energy politics; Independent variables; Indirect effects; Perceived benefits; Political factors; Political ideologies; Political variables; Acceptance of solar energy; Energy politics; Energy security; Risk perception